Erratum to “Neutron–19C scattering: Emergence of universal properties in a finite range potential” [Phys. Lett. B 764 (2017) 196-202](S0370269316306931)(10.1016/j.physletb.2016.11.030) - Shalchi, M. A. [UNESP]; Yamashita, M. T. [UNESP]; Hadizadeh, M. R.; Frederico, T.; Tomio, Lauro [UNESP] (Elsevier, 2017)
Numerical results for the function (1−EK/E0)kcot⁡δ0 R, as given in Phys. Lett. B 764 (2017) 196, are revised. Fig. 2 and Tables 2 and 3 should be replaced by the following corresponding figure and tables. The conclusions of the original paper remain unchanged.
Keywords: Efimov physics; Faddeev equation; Halo nuclei; Scattering theory